Research on physical fitness characteristics of outstanding male long jumpers in china - Wei, P.; Yuan, T.; Gao, D.; Han, D. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: With the development of competitive sports, physical fitness has been increasingly valued, especially in track and field, a discipline heavily reliant on running and jumping abilities. In China, physical fitness testing is conducted for athletes based on the characteristics of their respective events to assess their physical fitness levels. This study aims to investigate the correlation between various physical fitness indicators and the performance of male elite jumping athletes. METHODS: Eight male elite athletes from the Chinese national track and field jumping team were selected for physical fitness testing, which included 30-meter sprint, 60-meter sprint, shot put, 1-repetition maximum (1RM) for bench press, 1RM for squat, 1RM for deadlift, 3000-meter run/2000-meter ergometer, weighted one-legged stance, back muscle endurance, and standing broad jump. The scores of the ten physical fitness test items were quantified uniformly according to the standards set by the Chinese Athletics Association. Pearson correlation coefficient was used to examine the correlation between the experimental data, exploring the relationships among the various indicators to gain new insights. RESULTS: The Pearson correlation coefficients (r) for 30-meter sprint, 60-meter sprint, shot put, and bench press maximum strength were all *0.8, showing a significant positive correlation, indicating a higher correlation between the performance in these four exercises and event-specific performance. The r values for relative strength in bench press, maximum strength in squat, and weighted one-legged stance were *0.5, indicating a moderate positive correlation with event-specific performance. The r values for 2000-meter ergometer/3000-meter run and standing broad jump were *0.3, indicating a weak correlation between these test scores and event-specific performance, statistically interpreted as unrelated. The r value for total physical fitness test score was *0.8, indicating a high positive correlation between overall test score and individual performance. CONCLUSION: Among the physical fitness test items, 30-meter sprint, 60-meter sprint, shot put, and bench press maximum strength show higher correlation with the performance of elite jumping athletes. Relative strength in bench press, maximum strength in squat, and weighted one-legged stance exhibit moderate correlation with athlete performance. The performance in 2000-meter ergometer/3000-meter run and standing broad jump shows weak correlation with event-specific performance. The results of physical fitness testing can to some extent reflect the physical fitness level and event-specific performance of athletes.